EFFECTIVE TREATMENT OF ACUTE VIRAL DISEASES: CURRENT OPINION IN PEDIATRICS AND OTORHINOLARYNGOLOGY (Медицинский совет, 2018)
Symposium “Recurrent respiratory syndrome: a common cold or real threat?” was held as part of the XVI Russian Congress with international participation “Innovative technologies in pediatrics and pediatric surgery. Resolved and unresolved issues”. The head of the Otorhinolaryngology Department of Pirogov Russian National Research Medical University, Corresponding Member, Professor M.R. Bogomilsky and the head of Paediatrics Department of Russian Medical Academy of Continuing Vocational Education GBOU DPO Professor I.N. Zakharova, who ran the symposium, stressed that considerable interest of pediatricians and otolaryngologists in the symposium was understandable, because the routine practice of these particular specialists was closely related to the treatment of respiratory diseases in children. After the symposium was over, we turned to the experts, who took part in it, and questioned them closely about the optimal therapeutic choice for respiratory diseases in children.